Sports Training Planning in Central American and Caribbean School Games Armenia 2013 (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2017)
With the aim of understanding the characteristics of training planning used by coaches participating in the Central American and Caribbean School Games held in Armenia, Colombia, between October and November 2013, a quantitative, prospective, observational study was conducted with a descriptive and relational scope, using a cross-sectional design. A survey developed by the research group was applied to a non-probabilistic sample of 41 coaches (35 men, 6 women) from 13 sports disciplines, representing the nine participating delegations (countries), with a mean age of 42.1 ± 11.9 years. Descriptive statistics were performed to analyze frequencies, measures of central tendency, and relationships using SPSS v. 20.The results regarding the time frame of their planning showed a preference for long-term planning. Regarding the criteria for determining the planning model to follow, most coaches used all proposed criteria (objectives, calendar, and athletes). Concerning the use of models present in the literature, affirmative responses predominated, with macrocycles being the most commonly used. In conclusion, the planning time employed was predominantly long-term; the criteria for determining the planning model followed, in order of importance, were all criteria, competitive objectives, and the competition calendar. The vast majority of coaches have knowledge of and use one of the planning models known in the specialized literature.